Make Modernist Sexes, Genders, and Sexualities New (KULT_online, 2020)
The goal of Modernism, Sex, and Gender by Celia Marshik and Allison Pease is to introduce readers and researchers to a debate about modernism spanning over a century in which sex, gender, and sexuality played and still play a constitutive role in the processes of understanding modernism. It does so by tracing how the changing ideas of gender and sexuality in concatenation with the recovery of forgotten, mostly women, authors altered the course of the conceptualizations of modernism in literary criticism, beginning with T. S. Eliot and F. R. Leavis, through the landmark studies of the second wave feminism, all the way through to the last two decades. One of the greatest achievements of Modernism, Sex, and Gender is its meticulous recording of the conjunction of shifts in modernist, as well as feminist criticism, queer theory, and masculinity studies, all of which – from a multitude of viewpoints – prove that sexes, genders, and sexualities are not only one of the many thematic interests of modernist criticism, but unavoidable and central to the very definition of modernism, despite its changes during the decades.